1986
DOI: 10.1159/000173981
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Walk-Through Angina Phenomenon during Exercise Testing

Abstract: Out of 3,900 patients who performed an exercise test at our clinic, 3 patients demonstrated a walk-through phenomenon (WTP), defined as the occurrence of mild angina during the first stages of exercise with disappearance of chest pain at higher workloads despite a greater pressure-rate product. 2 patients had variant angina, one with normal coronary arteries and the other with single vessel disease, while the third patient had stable exertional angina and a severe coronary artery disease with occlusion of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…These patients had the ability to continue walking after the on set of angina with eventual disappearance or lessening of anginal pain associated with im provement of the ischemic ST segment de pression. Gavazzi et al [3] also reported a case who had a severe coronary artery dis ease with occlusion of 2 major vessels retrogradely filled by collateral channels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These patients had the ability to continue walking after the on set of angina with eventual disappearance or lessening of anginal pain associated with im provement of the ischemic ST segment de pression. Gavazzi et al [3] also reported a case who had a severe coronary artery dis ease with occlusion of 2 major vessels retrogradely filled by collateral channels.…”
Section: Discussionmentioning
confidence: 97%
“…The walk-through phenomenon is explained by a gradual increase in blood supply to the jeopardized myocardium in the presence of unchanged or increased myocardial oxygen requirement [1][2][3]. This is accomplished by two different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Bywa też, że podczas trwania wysiłku ból mija i pacjent kontynuuje aktywność bez dolegliwości (walk-through angina). Nie jest znany dokładny mechanizm tych zjawisk, choć większość badaczy wiąże je z hartowaniem mięśnia sercowego przez niedokrwienie (preconditioning) (5)(6)(7) . Wysiłkowe bóle dławicowe pojawiają się zwykle, gdy blaszka miażdżycowa zajmuje co najmniej 50% średnicy światła tętnicy nasierdziowej.…”
Section: Ból Dławicowyunclassified
“…In 'walk -through angina' phenomenon, patient develops angina in the initial phase of exertion, However, if the patient continues to walk, angina gradually disappears. [1][2][3][4][5][6][7] Appreciation of this phenomenon is important because relief in anginal discomfort with continuation of effort may mislead the patient as well as a clinician against the diagnosis of angina on effort. This is important because this phenomenon can occur even in the presence of severe coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because this phenomenon can occur even in the presence of severe coronary artery disease. 3,4 Appreciation in also important because some of these patients may show significant improvement in exercise tolerance with exercise training. 4 Documentation of walk-through phenomenon during exercise testing is rare.3 Mac Alpin and Kattus 14 studied twelve patients of angina.…”
Section: Introductionmentioning
confidence: 99%